A Swallow Preservation Protocol Improves Function for Veterans Receiving Chemoradiation for Head and Neck Cancer. (31st March 2015) - Peng, Kevin A.; Kuan, Edward C.; Unger, Lindsey; Lorentz, William C.; Wang, Marilene B.; Long, Jennifer L.
Abstract : Objective: Determine the efficacy of a swallow preservation protocol (SPP) on maintaining swallow function in patients undergoing chemoradiation (CRT) or radiation therapy alone (RT) for head and neck squamous cell carcinoma (HNSCC). Study design: Retrospective case series. Setting: Veterans Affairs medical center. Subjects and Methods: Patients treated with CRT or RT for HNSCC between February 2006 and November 2013 were studied. Those enrolled in the SPP participated in swallowing, jaw, and tongue exercises during cancer therapy. The comparator group received no swallowing intervention during CRT. A previously described functional outcome swallowing scale (FOSS; 0 = no symptoms and 5 = nonoral feeding for all nutrition) was used to quantify dysphagia prior to and at the completion of cancer therapy, and an analysis was performed to compare swallowing function. Results: Forty‐one (all male; mean age, 66 years) and 66 patients (all male; mean age, 61 years) were included in the SPP and comparator groups, respectively. In the SPP group, mean pre‐ and posttreatment FOSS scores were 2.2 and 2.2, respectively, while the corresponding scores in the comparator group were 1.8 and 2.7, respectively, with posttreatment FOSS scores being significantly worse than pretreatment FOSS scores in the comparator group only. Conclusion: Patients enrolled in the SPP demonstrated preserved swallowing function over the course of cancer treatment compared with a comparator group. This confirms the importance of early evaluation and intervention for dysphagia prior to and during CRT or RT alone.